Development and Validation of Q-Absorbance Ratio UV Spectrophotometric Method for Simultaneous Determination of Bisoprolol Fumarate and Cilnidipine in Marketed Formulation Besicor C5 - Mishra, Pranali (Asian Journal of Pharmaceutics (AJP), 2022)
Introduction: Cardiovascular disorders involve simultaneous administration of more than one drug; hence, numerous combinations, including calcium channel blockers and beta-blockers, are available in the market and are approved by various regulating authorities. Cilnidipine (CLD), a calcium-channel blocker, and Bisoprolol fumarate, a β1-adrenergic receptor blocking agent are such combinations available on the market. This combination is used in the treatment of hypertension and angina pectoris. Therefore, these drugs must be accurately analyzed in various samples, including laboratory mixtures and marketed formulations. Methods: Simultaneous estimation of Bisoprolol fumarate and CLD in marketed formulation Basicore C5 was carried out using the UV spectrophotometric method in ethanol. The Q-Absorbance ratio method was selected for estimation. The wavelengths used were 224.5 nm, λmax of Bisoprolol fumarate, and 232 nm, an iso-absorptive point of both the drugs. Results: Beer’s law was obeyed in the concentration range between 2 and 10 μg/mL for both the drugs. Recovery studies have validated the analysis results as per ICH guidelines. Accuracy was found between 99.3–99.75% and 99.48–100.06% for Bisoprolol fumarate and CLD, respectively. The limit of detection was 0.0943 and 0.0751 μg/mL for Bisoprolol fumarate, while 0.0355 and 0.1141 μg/mL for CLD at 224.5 and 232 nm, respectively. The limit of quantifications was 0.2860 and 0.8983 μg/mL for Bisoprolol fumarate, while 0.1610 and 0.3457 μg/mL for CLD at 224.5 and 232 nm, respectively. Conclusion: The method was simple, reproducible, rapid, and precise. Hence, it could analyze laboratory samples and marketed formulations containing these two drugs.